Ni2Al3 intermetallic coating: microstructure and mechanical properties. Issue 2 (3rd April 2018) - Li, Ningning; Wang, Minzhi; Zheng, Gong; Li, Pei; Li, Yongsheng; Chen, Guang
Abstract: The Ni-Al intermetallic coating was prepared by adopting a two-step method, which consist of electroplating nickel previously and then by pack aluminizing. The mechanical properties, namely the hardness ( H ) and elastic modulus ( E ), were measured by the nanoindentation test. The X-ray diffraction analysis shows that the coating is mainly composed of Ni2 Al3 . The thickness of the Ni2 Al3 intermetallic coating prepared on the substrate is about 35 μm, and it has a good metallurgical bond with the substrate from the SEM morphology. The hardness and elastic modulus of the Ni2 Al3 intermetallic coating are about 14.66 and 229.03 GPa, which are obviously higher than that of the substrate. The area surrounded by the load-penetration depth curve of the Ni2 Al3 coating is more compact than that of the substrate. The indentation creep of the coating is also small.